The Feasibility of Optimal Surgical Result Prediction according to the Centre of Rotation Shift after Multilevel Cervical Total Disc Replacement - Jun Ho Lee (Neurologico Spinale Medico Chirurgico, 2018)
Objective: This study investigates the relation between shifted locations of centre of rotation (COR) at each cervical level and subsequent surgical outcomes after multilevel cervical total disc replacement (MCTDR) and identifies radiological parameter that corresponded to change of COR after MCTDR. Methods: The study included a consecutive series of 24 patients who were treated with MCTDR following diagnosis of multilevel cervical disc herniation or stenosis. Numeric rating scale (NRS), range of motion (ROM) at both C2-7 segment and TDR implanted levels, and the location of COR at TDR implanted level were evaluated at pre- and post-MCTDR. These parameters were compared between patients who experienced successful and unsuccessful pain relief. Results: The inherent CORs relatively at ventro-cranial coordinates have demonstrated significant migrations to dorso-caudal locations at each cervical levels, more prominent shifts for the successful group, after MCTDR switch. The unsuccessful group showed markedly reduced C2-7 ROM and reduced angular improvement at C2-7 as well as MCTDR level after surgery in comparison with the successful group. Postoperative C2-7 ROM was related to postoperative COR along the X-axis. Conclusions: The crucial determinants for clinical success after MCTDR, other than mere preservation of the ROM both at C2-7 and TDR implanted levels, was the restoration of COR from ventro-cranial location at degenerated cervical motion segment close to normal coordinates by posterior and inferior shifts after MCTDR. The position of COR along the X-axis after MCTDR was an important factor to determine maintenance of C2-7 RO.